"Active" and "passive" ecological restoration strategies in meta‐analysis. Issue 5 (5th September 2020) - Atkinson, Joe; Bonser, Stephen P.
Abstract : One of the means of creating a more robust methodology for ecological restoration involves reducing the gap between ecological theory and restoration practices. A common strategy to do so is using meta‐analysis to understand key drivers of restoration outcomes. "Active" and "passive" is a dichotomy often used to separate restoration strategies in such meta‐analyses. We investigate previously raised concerns about selection bias and subjective categorization of strategies. We promote a paired experimental design in future empirical research and propose the use of three categories of restoration strategy in lieu of "passive" and "active" to alleviate inconsistency in definitions and categorization.